Impact of self-financed rotavirus vaccination on acute gastroenteritis in young children in Turkey - Erdem Gönüllü; Ahmet Soysal; İsmail Yıldız; Metin Karaböcüoğlu (Taylor & Francis Group, 2021)
Rotavirus (RV) vaccines have been available in Turkey since 2006. These vaccines are not funded by the National Health System, so consequently their coverage rate in children has reached only 13-18%. We conducted a retrospective record review including all children ≤60 months of age presenting to study hospitals with suspected or clinical acute gastroenteritis (AGE) between 2012 and 2018. During the study, 109,605 children ≤60 months of age were admitted to pediatric out-patient clinics and pediatric emergency room, of which 15,501 (14%) were diagnosed with AGE. Incidence of RV-positive AGE decreased from 4.47 per 1,000 children in 2012 to 2.48 per 1,000 in 2018. A total of 4,805 (31%) such children were hospitalized with RV-positive AGE, a decrease from 1.9 per 1,000 children in 2012 to 0,45 per 1,000 in 2018. The length of hospital stays (LOS) of RV-positive AGE was 2.47 ± 1.15 days compared to LOS of RV-negative AGE 1.59 ± 1.17 days (p < .001). The overall cost of RV-positive AGE ($335 ± 200) was higher than that for RV-negative AGE ($280 ± 148) cases (p = .015). Vaccine effectiveness against any case of RV-positive AGE was 75,1% (95% CI: 65-86%). Despite the low level of vaccine coverage, the introduction of RV vaccination had a positive impact on the incidence of RV-positive AGE and related hospitalizations in young children.